Validation of a multiplex system with 20 multi-Indels for forensic purposes. (December 2015) - Song, F.; Luo, H.B.; Li, J.N.; Hou, Y.P.
Abstract: Multi-Indel polymorphism has been considered as a useful supplementary tool for human identification. Compared with the conventional single Indel marker, it has showed obvious advantage in improving the discrimination power. Previously, we established a novel multiplex system with 20 multi-Indels witch contains 43 single InDel markers. Currently, validation studies were performed with species specificity, sensitivity, mixture study and artificially degraded samples, according to the FBI/SWGDAM guideline. The results showed (a) no fluorescent signal for forensically relevant animals was obtained, (b) complete and accurate profiles were detectable as DNA amount was 0.3 ng, and (c) the reliable results of typing 20 multi-Indels could be obtained from degraded DNA. The mixture of two unrelated individuals in a ratio up to 3:7 could be recognized with all alleles. In conclusion, this study demonstrated that the multiplex system with 20 multi-Indels can be used as a useful supplementary method for human identification and paternity testing.